Conservation International and Hewlett Packard Enterprise - Bourg-Meyer, Vero; Elias, Jaan; Chevalier, Judith A. (London : Yale School of Management, 2018)
In 2017, Conservation International (CI) and Hewlett-Packard (HPQ), which had collaborated on building a software platform named the Wildlife Management Analytics system or WMA, were looking for a way to market the product. HPQ had licensed the software to CI and the nonprofit believed that the best way to distribute the WMA was to sell access to the software, offsetting some of its costs. CI confronted a number of important questions in trying to implement their plan. How should CI determine pricing for the software while advancing its objectives as a nonprofit organization? How did this initiative fit into CI's advocacy work and mission? Whom should CI charge for the use of the software, and what factors should they take into account when deciding how much to charge? And with scientists increasingly wary of environmental organizations pushing an agenda at the expense of what academics saw as intellectual honesty, would CI be able to drum up enough enthusiasm for the solution?
Originally Published InBourg-Meyer, V., Elias, J., & Chevalier, J. (2018). Conservation International and Hewlett Packard Enterprise. Yale SOM Case 17-201 New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Conservation International; Hewlett-Packard Company; Nonprofit organizations -- Marketing